2015
DOI: 10.1007/s13365-015-0315-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytomegalovirus infection in human neural precursor cells depend on their differentiation state

Abstract: Cytomegalovirus (CMV) is the most common cause of congenital infection in developed countries and a major cause of neurological disability in children. Although CMV can affect multiple organs, the most important sequelae of intrauterine infection are related to lesions of the central nervous system. However, little is known about the pathogenesis and the cellular events responsible for neuronal damage in infants with congenital infection. Some studies have demonstrated that neural precursor cells (NPCs) show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 37 publications
2
19
0
1
Order By: Relevance
“…Neural cell number and maturely differentiated neural cells are the foundation for fetal brain development. Researchers have found that human cytomegalovirus (HCMV), the leading cause of central nervous system disorders following congenital infection, can infect and replicate in neural progenitor cells (NPC), thereby causing neural cell loss and premature differentiation, perturbing NPC fate, and leading to brain malformations [16,17]. T. gondii is known to be capable of invading almost any nucleated cells, and is a critical factor relevantly causing brain pathological damage.…”
Section: Discussionmentioning
confidence: 99%
“…Neural cell number and maturely differentiated neural cells are the foundation for fetal brain development. Researchers have found that human cytomegalovirus (HCMV), the leading cause of central nervous system disorders following congenital infection, can infect and replicate in neural progenitor cells (NPC), thereby causing neural cell loss and premature differentiation, perturbing NPC fate, and leading to brain malformations [16,17]. T. gondii is known to be capable of invading almost any nucleated cells, and is a critical factor relevantly causing brain pathological damage.…”
Section: Discussionmentioning
confidence: 99%
“…Neural stem/progenitor cells (NSPCs) are capable of self‐renewal and differentiation into neurons, astrocytes, or oligodendrocytes. During CNS insults (viral infection, stroke, protein misfolding stress), the NSPC pool can expand or contract (Chucair‐Elliott et al, ; Das and Basu, ; Das et al, ; Deierborg et al, ; Gonzalez‐Sanchez et al, ; Hoglinger et al, ; Lee et al, ; Sun et al, ). During many neurotropic infections, NSPC proliferation and neurogenesis declines (Mutnal et al, ; Ruller et al, ; Sharma et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…NPCs derived from induced pluripotent stem cells (iPSCs) and fetal stem cells are fully permissive for HCMV infection (8)(9)(10)(11), with susceptibility influenced by the degree of differentiation (12,13). Expression of viral genes has been shown to alter signaling pathways and expression of key development factors, including Notch and Sox2 (14)(15)(16), and infection results in abnormal proliferation and differentiation (13,17,18). For the pluripotency factor Sox2, expression of HCMV IE1 causes downregulation of Sox2, involving IE1 sequestration of unphosphorylated STAT3 to the nucleus (15,19).…”
mentioning
confidence: 99%